The changing dynamics of US inflation persistence: A quantile regression approach - Peter Tillmann; Maik H. Wolters (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
We examine both the degree and the structural stability of inflation persistence at different quantiles of the conditional inflation distribution. Previous research focused exclusively on persistence at the conditional mean of the inflation rate. Economic theory, however, provides various reasons -for example downward wage rigidities or menu costs- to expect higher inflation persistence at the upper than at the lower tail of the conditional inflation distribution. Based on post-war US data we indeed find slower mean reversion in response to positive than to negative shocks. We find robust evidence for a structural break in persistence at all quantiles of the inflation process in the early 1980s. Inflation persistence has decreased and become more homogeneous across quantiles. Persistence at the conditional mean became more informative about the degree of persistence across the entire conditional inflation distribution. While prior to the 1980s inflation was not mean reverting in response to large positive shocks, our evidence strongly suggests that since the end of the Volcker disinflation the unit root can be rejected at every quantile including the upper tail of the conditional inflation distribution.
Keywords: E31; E58; C32; 330; inflation persistence; quantile regressions; structural breaks; monetary policy; Federal Reserve; Inflationsrate; Inflation; Hysteresis; Strukturbruch; Schätzung; USA